Penegakan Hukum Oleh Kejaksaan Tinggi Sumatera Barat Terhadap Tindak Pidana Narkotika No.582./PID.SUS/2023/PN.PDG - Fitri Ramadhani; Elwidarifa Marwenny (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The misuse of narcotics continues to rise, as reported by the National Narcotics Agency (BNN) of Indonesia. Narcotics cases from 2020 to 2022 increased from 833 to 879 cases. According to the latest data from BNN in 2023, the province of West Sumatra recorded 65 thousand of its residents involved in narcotics cases. This number places West Sumatra sixth in the highest narcotics cases in Indonesia. Therefore, serious efforts from various parties are required to address this issue. One such case handled by the High Prosecutor's Office of West Sumatra is Case No. 582/Pid.Sus/2023/Pn.Pdg. Based on the results of the discussion, the research questions in this study include: 1) What was the basis for not prosecuting the defendant as a narcotics abuser? 2) What preventive measures can the High Prosecutor's Office of West Sumatra take to reduce the circulation of narcotics? To answer these questions, the study uses an Empirical Legal research method with semi-structured interviews. The approach used is a case study, and it can be concluded that: 1) The prosecutor’s consideration in case No. 582/Pid.Sus/2023/Pn.Pdg was based on Article 114 paragraph (1) of the Narcotics Law and Supreme Court Circular Letter (SEMA) No. 4 of 2010 regarding the placement of narcotics abusers, victims, and addicts into rehabilitation institutions; 2) Preventive measures that the High Prosecutor’s Office of West Sumatra can take to reduce narcotics circulation include conducting socialization to the public and schools, implementing rehabilitation for narcotics abusers, and providing training so that narcotics abuse victims can acquire skills to meet their life needs.